Ban the Black Box: Criminal Background Screening and the Information-Withholding Problem - Stocker, Jennifer (2019)
Beverly Harrison worked for the city of Dallas, Texas, for twenty-eight years before she retired to devote more time to her grandchildren and her church. In 2013, Harrison took a job as a crossing guard for Dallas County Schools to supplement her retirement income. Eight days into her new role, Harrison was terminated. The cause? A nearly forty-year-old assault conviction on her background check, stemming from an altercation when Harrison was just eighteen. Although Harrison’s criminal record had not barred her from a long career in public service or several years as a home health aide, she was dismissed from her new role without discussion. With an increasing number of employers performing background checks on potential employees, stories like Harrison’s are all too common. When a candidate fills out a job application, often one of the questions she will encounter is, “Have you ever been convicted of a crime?” A “yes” may spell the end of her candidacy. Even when a candidate makes it through the selection process, like Harrison, she may find that a criminal record stands in the way of continued employment. An inability to obtain employment is one of the collateral consequences that affects an individual’s ability to reintegrate into society following criminal conviction. As in Harrison’s case, the barrier to employment can persist for years or even decades. This is a problem for a large and still-growing segment of the population, as a result of the “tough-on-crime” policies prevalent in the 1980s and 1990s.11 These policies have disproportionately affected racial minorities—particularly black and Hispanic men—exacerbating the challenges they already face in obtaining employment. Legislators have responded to these interlinking problems with laws to remove “the box,” the criminal-record question on job application forms. The fundamental theory of “Ban the Box” (BTB) laws is that if a candidate with a criminal record is considered on his own merits before his criminal history is revealed, the employer will be more willing to hear him explain the circumstances of the offense and provide evidence of rehabilitation. BTB laws exist within a larger framework of employment laws designed to inhibit the flow of sensitive information that employers receive about potential employees. Like criminal records, some information that employers receive during the candidate selection process may disproportionately disadvantage minorities who already face obstacles to employment. As more of these types of laws are enacted, studies indicate that they may have the opposite of the intended effect. Recent research indicates that BTB laws may worsen employment outcomes for young black and Hispanic men. These studies conclude that, in the absence of concrete information, employers assume that minority candidates are more likely to have criminal records and decline to hire them. These findings have generated much discussion about the value of BTB laws. Reports suggest that they may hamper further BTB legislation. Some legal commentators have responded with calls to repeal BTB laws and pursue alternative means of redressing criminal-record discrimination. This Note examines the implications of these recent studies in the context of BTB’s goals. Part I traces the development of the BTB movement and surveys current political responses to the call to delay criminal-record inquiries. Part II examines recent research suggesting that BTB laws lead to an increase in race discrimination in hiring. Part III contextualizes this research within a broader theme of negative effects produced by withholding key information during the candidate selection process. This information-withholding problem surfaces on both sides, with employers and candidates alike relying on guesswork to find the right fit. Part IV recommends breaking through the mystification from the candidate’s side. By increasing the information available to the candidate, candidates can make more informed decisions about which jobs to seek, and employers will see the benefit of a stronger candidate pool